PENGARUH PEMBELAJARAN KOOPERATIF MODEL TEAM GAME TOURNAMENT (TGT) TERHADAP MOTIVASI BELAJAR PAK SISWA KELAS XI SMA SWASTA HKBP 1 TARUTUNG TAHUN PEMBELAJARAN 2019/2020 - Desi Raya Situmorang (IAKN Tarutung, 2020)
This study aims to determine how much influence the TGT Model Cooperative Learning Against PAK Learning Motivation of Class XI Students in HKBP 1 Tarutung Private High School Year 2019/2020, with the hypothesis that there is a positive and significant effect of the TGT Model Cooperative Learning Against PAK Student Motivation in Class XI HKBP 1 Tarutung Private High School 2019/2020 Academic Year. This study uses a descriptive quantitative method approach, with a population of all students in class XI of HKBP 1 Tarutung Private High School, with a total of 150 people with a sample of 48 people. Data were collected with 45 questionnaire items compiled by the author based on variable indicators according to expert theory. The questionnaire test was conducted on 30 students outside the study sample, and its validity and reliability were tested. The results of the data analysis showed that there was a positive and significant effect between the TGT Model Cooperative Learning Against PAK Learning Motivation for Class XI Students in the HKBP 1 Tarutung Private High School in 2019/2020 with a coefficient of determination R2 = 32.3% and a significant test of influence was obtained by Fhitun Ftable of 53.35 4.08, meaning that H0 is rejected and Ha is accepted. This study suggests that for good student motivation in classroom learning, the TGT Model Cooperative Learning is well implemented.Keywords: Cooperative Learning Model Team Game Tournament, (TGT) Student Learning Motivation